Genetic Analysis of Two Bile Salt Hydrolase Activities in Lactobacillus acidophilus NCFM - McAuliffe, Olivia (American Society for Microbiology, 2005)
Two genes, bshA and bshB, encoding bile salt hydrolase enzymes (EC 3.5.1.24) were identified in the genome sequence of Lactobacillus acidophilus NCFM. Targeted inactivation of these genes via chromosomal insertion of an integration vector demonstrated different substrate specificities for these two enzymes.